2000
DOI: 10.1021/jp993156y
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Production in the Oscillatory Bray−Liebhafsky Reaction

Abstract: The volume of gaseous oxygen produced during the Bray-Liebhafsky (BL) oscillating reaction was measured. The rates of oscillatory O 2 evolution were calculated and the geometrical effects of the Pt electrode surface, stirring rate, and addition of the surfactant on the oscillatory behavior were studied. A significant stirring rate and detergent effect is observed. The oxygen evolution results obtained are in satisfactory agreement with oscillatory behavior of the BL reaction monitored by potentiometric measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 25 publications
(53 reference statements)
1
13
0
Order By: Relevance
“…The second hole was for a glass tube (diameter 0.5 cm), which was connected via tubing to a 250-mL closed Erlenmeyer-like flask reservoir containing 220 mL of water placed above the level of the reaction vessel. The details of our experimental arrangement for measuring the production of oxygen in the BL system were designed in our previous work …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The second hole was for a glass tube (diameter 0.5 cm), which was connected via tubing to a 250-mL closed Erlenmeyer-like flask reservoir containing 220 mL of water placed above the level of the reaction vessel. The details of our experimental arrangement for measuring the production of oxygen in the BL system were designed in our previous work …”
Section: Methodsmentioning
confidence: 99%
“…We were able to calculate the rates of oxygen evolution and to study the effects of the stirring rate on the rate of oxygen production and on the oscillations in the BR reaction. In our earlier papers on the BL reaction, , we showed that the rate of interphase transport of I 2 and O 2 can be greatly influenced by stirring and that such physical processes can inhibit oscillations.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although a large number of works [11][12][13][14] devoted to the mechanism of the BL reaction for a long time, the overall mechanism has still not been elucidated, and is complicated by the fact that the system is also sensitive to light [15], pressure and stirring [16,17], microwaves [18,19] and oxygen [20,21]. It seems to be too difficult to obtain enough relevant information on the kinetics of this system.…”
Section: Introductionmentioning
confidence: 99%
“…However, one process might be faster than the other during a short interval. Processes (B) and (C) alternately dominate over the whole system and result in the concentration of iodine and the rate of oxygen gas evolution change periodically [9][10][11][12]. Although the overall stoichiometry of the BL reaction seems to be simple, it is not easy to describe the mechanism.…”
Section: Introductionmentioning
confidence: 99%